Whence Came These Plants Most Foul? Phylogenomics and Biogeography of Lowiaceae (Zingiberales) - Niissalo, Matti A.; Gardner, Elliot M.; Khew, Gillian S.; Šída, Otakar; Poulsen, Axel Dalberg; Leong-Škorničková, Jana (Frontiers in Ecology and Evolution, 2022)
Lowiaceae (order Zingiberales) is a small family of forest herbs in Southeast Asia. All species belong to the genus Orchidantha. They are known for possessing orchid-like flowers that are smelly, apparently mimicking dead animals, faeces, or mushrooms. Little is known of the biogeographic patterns or character evolution of the family. We sampled the family extensively, including many recently discovered species, and reconstructed the phylogeny of the family using HybSeq with Lowiaceae-specific RNA baits. Our phylogenetic reconstructions confirm that the family is most closely related to Strelitziaceae, and that species with dark, foul-smelling flowers form a grade in which a clade of species with paler smelling flowers are embedded. The pale-flowered species produce a distinct odour, resembling edible mushrooms. Apart from a single species, the species from Borneo form a clade, and the same is true for Indochinese species. The remaining species form a more widespread clade. A biogeographic analysis shows that the distribution of Lowiaceae can explained by vicariance and gradual dispersal from a shared ancestral range of Borneo and Indochina. There is no evidence of long-distance dispersal, only a later extension in distribution to Peninsular Malaysia which coincides with the presence of a land bridge. Different directions of spread are possible, but none require long-distance dispersal. The results are consistent with the geological history of Southeast Asia. In particular, the relatively early isolation between Indochina and Borneo could be explained by the presence of a sea barrier that developed 10–15 MYA, and the continuous movement of plant species between Borneo and Peninsular Malaysia could be explained by a land bridge that existed until c. 5 MYA. The lack of an extensive land bridge with a suitable habitat may explain the absence of this genus from Sumatra and other Indonesian islands aside from Borneo. The strict reliance on a continuous habitat for the range expansion of Lowiaceae can be explained by their fruits and seeds, which lack obvious adaptations for long-distance dispersal. The inability to disperse to new areas may also explain why the extant species have very restricted distributions.